Pengaruh Fasilitas Layanan Internet Banking Dan Mobile Banking Terhadap Kepuasan Nasabah Bank Syariah Indonesia Kantor Cabang Tangerang - Sabik Khumaini; Fahrudin Fahrudin; Samsuri Samsuri (Al Maal: Journal of Islamic Economics and Banking, 2022)
This research aims to determine the effect of internet banking and mobile banking service facilities on customer satisfaction at Indonesia Islamic Bank Tangerang branch office. This type of research is field research with a quantitative, the data collection technique used in this research is the questionnaire data collection method. The population in this study were 500 customers using internet banking and mobile banking, and the sample in this study was 85 respondents using random sampling. The results showed that based on the partial t test, there is a significant effect of internet banking service facilities on customer satisfaction and has a positive relationship. And there is a significant effect of mobile banking on customer satisfaction and has a positive relationship. And based on the simultaneous F test, there is a significant effect of internet banking and mobile banking service facilities on customer satisfaction with an F count of 128.777 with a significance value of F of 0.000. And based on the R test determination of 75.9% the ability of the independent variables to explain the variance of the dependent variable.